(untitled) (The Journal of Psychology and Sociology, 2023)
This article presents results of empirical study aimed at studying the place of a safe psychological environment at school in development of personality of children, as well as the development of practical proposals and recommendations for creating a safe environment in school environment. It was revealed that the "initiators" and "defenders" of bullying had a high level of verbal thinking, and, conversely, a low level of verbal thinking - among the " assistants" and "observers" of bullying. Boys and girls, in general, are equally likely to experience bullying. However, physical bullying is more common among boys, while verbal bullying is more common among girls. The "defenders" and "initiators" of bullying have a low level of anxiety, while the "victims", " assistants" and "observers" of bullying, on the contrary, have a high level of anxiety. On the basis of the results obtained, practical recommendations were developed for psychologists, school management and parents on the problem of creating a safe environment at school. In particular, some ways of working effectively with pupils of early and older adolescence are proposed. And also on the basis of G. Kasper’s questionnaire "Studying mobbing at school", the author’s method for assessing the experience of bullying among adolescents is proposed. Keywords: adolescence, bullying, physical bullying, verbal bullying, "initiator", "victim", "defender", "assistant", "observer".